Imperative Role of Geo-Economic Factors in Developing Efficiency of Agricultural Marketing - Dr Rajeev Kumar (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Agricultural marketing consists of two wordsi.e. “agriculture” and “marketing”. The first word agriculture means producing the agro food products with the use of natural factors for the welfare of human. It is fully depending on natural processing. The second word marketing refers to the activities that are done by the business organizations to promote their products and services to their targeted customers. In marketing the targeted customers can be attracted and maintained by creating strong customer values for them in the organization. It is possible through, effective market survey, market trending, better customer service and satisfaction, customer focus and continuous follow up. Agricultural marketing system is an efficient way by which the